Silencing of FAD synthase gene in Caenorhabditis elegans upsets protein homeostasis and impacts on complex behavioral patterns - Liuzzi, Vania C.; Giancaspero, Teresa A.; Gianazza, Elisabetta; Banfi, Cristina; Barile, Maria; De Giorgi, Carla (Biochimica et biophysica acta, 2012)
FAD synthase is a ubiquitous enzyme that catalyses the last step of FAD biosynthesis, allowing for the biogenesis of several flavoproteins. In humans different isoforms are generated by alternative splicing, isoform 1 being localized in mitochondria. Homology searching in Caenorabditis elegans leads to the identification of two human FAD synthase homologues, coded by the single copy gene R53.1. The C. elegans R53.1 gene was silenced by feeding. The expression level of transcripts was established by semi-quantitative RT-PCR. Overall protein composition was evaluated by two-dimensional electrophoresis. Enzymatic activities were measured by spectrophotometry and oxygen consumption by polarography on isolated mitochondria. From R53.1 two transcripts are generated by trans-splicing. Reducing by 50% the transcription efficiency of R53.1 by RNAi results in a 50% reduction in total flavin with decrease in ATP content and increase in ROS level. Significant phenotypical changes are noticed in knock-down nematodes. Among them, a significant impairment in locomotion behaviour possibly due to altered cholinergic transmission. At biochemical level, impairment of flavoenzyme activities and of some KCN-insensitive oxygen-consuming enzymes is detected. At proteomic level, at least 15 abundant proteins are affected by R53.1 gene silencing, among which superoxide dismutases. For the first time we addressed the existence of different isoforms of FAD-metabolizing enzymes in nematodes. A correlation between FAD synthase silencing and flavoenzyme derangement, energy shortage and redox balance impairment is apparent. In this aspect R53.1-interfered nematodes could provide an animal model system for studying human pathologies with alteration in flavin homeostasis/flavoenzyme biogenesis. ► R53.1 gene is transcribed via a trans-splicing mechanism in two mRNAs in C.elegans. ► Significant phenotypical changes are observed upon gene silencing. ► Dysregulation of many enzymes is observed with the decreased content of FAD. ► R53.1-interfered nematodes could provide an animal model system for studying human pathologies involving FAD deficiency.